Трансформация трагического: русская классика в мировоззренческих концепциях украинского модернизма - Halina Korbicz (Studia Rossica Posnaniensia)
This article describes the attitude of Ukrainian authors of the late 19th and early 20th century (Ivan Franko, Mykola Yevshan, Mykyta Sryblyans’kyi and others) toward the manifestations of tragedy in Russian literature of the 19th century. The primary focus is on Fyodor Dostoevsky’s anthropological discoveries, Nikolai Gogol’s existentialism and Leo Tolstoy’s psychologism. The ideas of these writers were considered conformable to the perception of the fin-de-siècle world with its tragic background and helped Ukrainian writers form their own philosophical and aesthetic views. Russian classics were studied with regard to realistic aesthetics and treated similarly to the classics of antiquity, i.e. as an unchanging value.